High-harmonic generation in metallic titanium nitride - A. Korobenko (Nature Portfolio, 2021)
High harmonic generation is a nonlinear optical phenomena and HHG from solid offers challenges and advantages over dilute media like gases. Here the authors report HHG from metallic thin film of titanium nitride and discuss the role of intraband current to HHG.